UiTM Mukah Bulletin: Inou Dengah UiTM Mukah? 1st Issue Edisi November 2022 / UiTM Cawangan Sarawak Kampus Mukah - UiTM Cawangan Sarawak, Kampus Mukah (Corporate Communication Unit, UiTM Mukah Campus, 2022)
It is with profound pleasure that we celebrate the launch of the inaugural edition of “Inou Dengah UiTM Mukah?”. ‘Inou dengah, ’ which translates to ‘what is up’, brings you essential news and updates about the UiTM Mukah Campus. The unique combination with the Melanau terminology ‘inou dengah’ is significantly related to the concept of connectedness that we forge with the local community. As the new Editor-in-Chief and on behalf of the Editorial Team, I would like to extend a warm welcome to the readers. With your support as readers, I see bright prospects for this Inou Dengah to serve the UiTM community better. I take this opportunity to thank our authors, editors, and all who have volunteered to contribute to the success of this inaugural publication. I close this message by inviting everyone to submit your articles. We hope to hear from you soon.